The Relationship Between Peer Social Support and Academic Procrastination in Class XI Students at Antartika 2 Sidoarjo Vocational School: Hubungan Antara Dukungan Sosial Teman Sebaya Dengan Prokrastinasi Akademik Pada Siswa Kelas XI di SMK Antartika 2 Sidoarjo - Widyanti, Ainur Niza Ayu; Indriani, Ririn Dewanti Dian Samudera (UMSIDA Preprints Server, 2023)
This study aims to determine the relationship between peer social support and academic procrastination in class XI students of Antarctica 2 Sidoarjo Vocational School. This type of research is quantitative using a correlational approach. The study population was grade XI students of SMK Antarctica 2 Sidoarjo, totaling 832 students. The research sample amounted to 260 students based on the Krejie & Morgan table with an error rate of 5%. The sampling technique in this study is using Simple Random Sampling. Data collection uses a Likert model scale for peer social support variables and procrastination adopted from previous research. The results of data analysis showed a correlation coefficient value of -0.276 with a significance of 0.000 <0.05, meaning that there is a negative relationship between peer social support and academic procrastination, so that the higher the peer social support, the lower the academic procrastination, and vice versa.